2017
DOI: 10.1371/journal.pone.0179104
|View full text |Cite
|
Sign up to set email alerts
|

Status of chemistry lab safety in Nepal

Abstract: Chemistry labs can become a dangerous environment for students as the lab exercises involve hazardous chemicals, glassware, and equipment. Approximately one hundred thousand students take chemistry laboratory classes annually in Nepal. We conducted a survey on chemical lab safety issues across Nepal. In this paper, we assess the safety policy and equipment, protocols and procedures followed, and waste disposal in chemistry teaching labs. Significant population of the respondents believed that there is no monit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

9
15
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(24 citation statements)
references
References 7 publications
9
15
0
Order By: Relevance
“…Four out of five of the participants (79.2%) had never received formal training in emergency response procedures. Lack of chemical laboratory safety training has been cited as a reason for science teachers' suboptimal safety awareness (Kandel et al, 2017). This aspect was confirmed when participants in this study requested blank questionnaires to keep in their laboratories as a safety reference.…”
Section: Discussion Of Resultssupporting
confidence: 59%
See 2 more Smart Citations
“…Four out of five of the participants (79.2%) had never received formal training in emergency response procedures. Lack of chemical laboratory safety training has been cited as a reason for science teachers' suboptimal safety awareness (Kandel et al, 2017). This aspect was confirmed when participants in this study requested blank questionnaires to keep in their laboratories as a safety reference.…”
Section: Discussion Of Resultssupporting
confidence: 59%
“…In addition to the indispensability of hands-on chemical experiments for learners in their learning of science, many studies also emphasise the importance of developing chemical safety awareness for both teachers and students (Eguna et al, 2011;Kandel et al, 2017). Sigmann (2018) points out that some laboratory activities in high school can be too risky when teachers have not been trained to conduct chemical experiments with groups of adolescents, or when laboratories lack proper emergency equipment or where there are no purpose-built laboratories to conduct the experiments.…”
Section: Pertinent Literature On Teachers' Chemical Laboratory Safetymentioning
confidence: 99%
See 1 more Smart Citation
“…In Nepal, a study concluded that there was improper disposal of chemical waste and the lack of monitoring the laboratory safety [16]. Likewise, Li [as cited [14]] stated that the liquid waste from all levels of school laboratories in Taiwan was around 1,691,100 liters in the year 2000 consisting of harmful wastes such as heavy metal liquid, organic liquid, acid and alkaline liquid waste.…”
Section: Introductionmentioning
confidence: 99%
“…In chemistry laboratories, instructors and students work with chemical substances and devices and are exposed to various risks (Kandel et al, 2017). For this reason, there is a requirement for a number of trainings and arrangements in order to minimize the harm by intervening risks that may occur in a conscious way.…”
Section: Introductionmentioning
confidence: 99%